2021
DOI: 10.1002/jha2.262
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐globin gene triplication and its effect in beta‐thalassemia carrier, sickle cell trait, and healthy individual

Abstract: The genotype and phenotype correlation between coinheritance of heterozygous beta‐thalassemia with the alpha‐globin triplication is unclear. In this study we have investigated and reviewed alpha triplication frequency in beta‐thalassemia carriers, sickle cell trait, and healthy individuals and its effect on hematological and phenotypical changes. In this study, 4005 beta‐thalassemia carriers, 455 sickle cell trait, and 2000 healthy individuals were included. Molecular characterization of beta and alpha‐thalass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 32 publications
0
15
1
Order By: Relevance
“…Four out of the 16 cases by Camashella et al, 15 had received blood transfusions. None of the 67 cases of Hamid et al, 11 or the six cases previously described from our center by Trehan et al had ever required a transfusion. Abedini et al, 14 reported that 10 (27.8%) of their cases had been intermittently transfused while 15 (41.7%) were regularly transfused.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…Four out of the 16 cases by Camashella et al, 15 had received blood transfusions. None of the 67 cases of Hamid et al, 11 or the six cases previously described from our center by Trehan et al had ever required a transfusion. Abedini et al, 14 reported that 10 (27.8%) of their cases had been intermittently transfused while 15 (41.7%) were regularly transfused.…”
Section: Discussionmentioning
confidence: 71%
“…The wide-ranging clinical phenotypes were also reported by Mehta et al, 18 with 25 index cases having a βTI-like syndrome, and 10 family members of index cases being asymptomatic. In contrast, Hamid et al, 11 from Iran reported that their all 67 subjects had βTT-like (mild/asymptomatic) phenotypes. However, another…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations